A Facile Method to Prepare Double‐Layer Isoporous Hollow Fiber Membrane by In Situ Hydrogen Bond Formation in the Spinning Line. Issue 5 (20th December 2015) - Noor, Nazia; Koll, Joachim; Radjabian, Maryam; Abetz, Clarissa; Abetz, Volker
Abstract : A double‐layer hollow fiber is fabricated where an isoporous surface of polystyrene‐ block ‐poly(4‐vinylpyridine) is fixed on a support layer by co‐extrusion. Due to the sulfonation of the support layer material, delamination of the two layers is suppressed without increasing the number of subsequent processing steps for isoporous composite membrane formation. Electron microscope‐energy‐dispersive X‐ray spectroscopy images unveil the existence of a high sulfur concentration in the interfacial region by which in‐process H‐bond formation between the layers is evidenced. For the very first time, our study reports a facile method to fabricate a sturdy isoporous double‐layer hollow fiber. Abstract : A facile method to fabricate a sturdy isoporous double‐layer hollow fiber by co‐extrusion is shown . Due to the sulfonation of the support layer material, delamination of two layers is suppressed by in‐process bond formation without the necessity to increase the number of subsequent processing steps for isoporous composite membrane formation.